Investigation of the Yellow River buried fault in the Wuhai basin, northwestern Ordos Block, China, using deep/shallow seismic reflection and drilling techniques. (1st September 2018) - Liang, Kuan; Sun, Changbin; Ma, Baoqi; Tian, Qinjian; Li, Dewen; Li, Dawei; He, Zhongtai
Graphical abstract: Highlights: Various detection methods were used to reveal the Yellow River buried Fault. Paleoseismic events can be identified in unequal thickness layers near faults. Drilling profiles reveal paleoseismic sequences and vertical slip rates of faults. The Wuhai Basin is extensional due to the relative movement of nearby plates. Abstract: Studying the faults in Wuhai Basin, which is located in the northwestern corner of the Ordos Block in China, can not only guide earthquake-safe construction in the region, but also provide a greater understanding of the structure of the Wuhai Basin and the dynamic environment of Northwestern Ordos Block. In this study, we effectively detected the Yellow River buried Fault (YRF), which we believe currently presents a risk to human life in the area. First, we laid out a deep seismic reflection profile (DSRP) in the north of the Wuhai Basin and found that the YRF is composed of two subparallel faults, the east branch of the Yellow River buried Fault (EYF) and the west branch of the Yellow River buried Fault (WYF), which formed a Y-type graben in the section. We then used 25 shallow seismic exploration profiles to find out how the faults are distributed. Finally, we used drillings and Quaternary dating methods to certify their existence and obtain their activity parameters. We used the sequence stratigraphy method to compare sediment strata and identified paleo-earthquake events by finding the unequal thickness layers (UTLs) on both sides of the fault. The drillings revealed that four earthquakes occurred on the YRF around 25.6 ± 0.11 ka BP, 39.5 ± 0.45–41.7 ± 0.57 ka BP, 58.25 ± 7.13 ka BP, and 111 ± 1.21 ka BP. Since the last activity on the YRF occurred much longer ago than its estimated recurrence cycle, we believe that the fault YRF currently presents a dangerous risk. Our study confirms that the YRF is a normal fault graben and that the Wuhai Bain is an extensional basin formed by the relative movement of the Tibetan Plateau, the Alashan Block, and the Ordos Block.